RELIGIOUS TOLERANCE REFLECTED IN SENIOR HIGH SCHOOL ELT TEXTBOOK: A CONTENT ANALYSIS - isyraqi, emyra moza (EDUCAFL: Journal on Education of English as Foreign Language, 2023)
Religious tolerance has become one of global issues in the world. So, Indonesia has regulation which specifies that the graduate competency standard for educational units for all grades is that students must accept the heterogeneity of faiths, communities, nations, races and classes. In this study, the textbooks which is published by the Educational Minister of Indonesia are also published under the category of Electronic School Books (ESB) in the form of electronic book (e-book). This study tried to examine the religious content reflected on three ELT textbooks currently used in Indonesia public high schools to teach Senior High School Students Grade X, XI, and XII            This research uses qualitative method with content analysis in analyzing the textbooks. This analysis is based on UNESCO (2017) checklist evaluation under the category of representation of diversity especially on religion. The data are collected by classifying contents in the textbooks based on the indicator list from UNESCO (2017).            Religious tolerance can happen within and across each religion because one religion can have so much different religious sect. The religious tolerance does not reflect quite well in the three textbooks because this study only relies on the indicator/recommendations from the UNESCO. The result shows that the textbooks do not provide enough information of each religion, learners do not have space and room to discuss or make a question about religion from the English textbook. The amount of space assigned to religious material in these textbooks are only provide four out of seven recommendations from the UNESCO and it is hardly noticeable to the learners. These textbooks still can be used but needs more additional materials to use in the school especially material that related to religious tolerance. It means that these textbooks are significant imbalance between religion groups exist in Indonesia as materials to support learning in the classroom.